Environmental Impact of Road Dualisation: A Case Study of Mokola-Ojoo Road in Ibadan (2013)
The impacts of the dualisation of Mokola - Ojoo road in Ibadan, Nigeria on the inhabitants, socio-economic activities, biological and air environment were studied using physical observation and questionnaire survey. The dualisation caused the demolition of some adjoining structures and historic site, displacement of the inhabitants, the pollution of air with dust and carbon monoxide and brought untold hardships on the road users. Although the long term benefit of the dualisation is well recognized, the negative impacts may as well reduce the benefit thus establishing the importance of conducting proper Environmental Impact Assessment prior to the commencement of the project.